DESIGN OF FRONTEND APPLICATION FOR CONTROLLING AND MONITORING VARIABLE FREQUENCY DRIVE - Nayan Dalvi; Pravin Gopale; Rajratna Lokhande; Pratik Patil; Prof.Nikhil Kasar (International Engineering Journal For Research & Development, 2023)
This project involves the development of a front-end application for a variable frequency drive. The application is designed to provide an intuitive user interface that allows the user to control the drive's operation and set various parameters such as frequency, voltage, and current limits. The project uses Modbus development platform and involves designing the user interface, developing the application, testing it for various scenarios, and deploying it for use. The project aims to create a user-friendly and functional application that meets the requirements of the user, making it easier to operate and control the variable frequency drive. With the help of this application a non-technical employee can learn VFD controls and working very efficiently. When it gets connected to laptop or PC’s using USB to Serial com port the user gets access to it. It shows the basic information of VFD and its manufacturing industry. The live parameters of it are also shown in an particular pop up block by which one can read all the parameters which are consisting in VFD.